Ziauddin Sardar: Membangun Epistemologi Islam - Ihsan, M. Taufik (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2023)
The lag behind Muslims from the West led to the emergence of the idea of the Islamization of science, which was initiated by one of them, al-Faruqi. However, this idea received criticism from Ziauddin Sardar. This criticism gave rise to the idea of